Analisis Implementasi Pelatihan Komunikasi Interpersonal Penggiat Anti Narkoba - Herny Novianti (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2023)
This study aims to analyze the implementation of interpersonal communication training for anti-drug activists in entrepreneurial circles, Cirebon city. The research method uses a combined method evaluation model between quantitative methods and qualitative methods (mixed-method), precisely explanatory mixedmethod design. Data collection uses interpersonal communication instruments which include: 1) openness; 2) empathy; 3) support; 4) positive attitude; 5) equality of will and communication. Overall it can be said that the interpersonal communication skills of anti-drug activists in the entrepreneurial environment of Cirebon City are in the "Fair" category with the acquisition of 45.49%. Interpersonal communication barriers experienced by anti-drug activists are semantic and psychological, physical barriers, status, frame of mind, and culture.